If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(2x + -2) = 16 Reorder the terms: 8(-2 + 2x) = 16 (-2 * 8 + 2x * 8) = 16 (-16 + 16x) = 16 Solving -16 + 16x = 16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + 16x = 16 + 16 Combine like terms: -16 + 16 = 0 0 + 16x = 16 + 16 16x = 16 + 16 Combine like terms: 16 + 16 = 32 16x = 32 Divide each side by '16'. x = 2 Simplifying x = 2
| 3x+8=4x+(15) | | 8x+4=4x-9 | | 4-x=16 | | -13X+3=23-3X | | 2x+8=2x+8 | | 2.3x-5=-1.7x-5 | | 31=4X+19 | | 7x-25=2x-15 | | 72=4m+10 | | y+5=2x | | -6x+4=-2 | | 7-3(x+2)=4 | | 5x-40=2-x | | 6w+5(w-2)=23 | | 6w+5(w-2)=33 | | 7x+12=120 | | 2p+3(p+3)=21 | | 7+4x=5x-12 | | 15+4(m-2)=21 | | 4(s+7)-8=10(s-4) | | -5b+24=-1 | | 2+3(x+1)=17 | | 10-4x=-x | | 16-3y+4y=27 | | 7c+3-5c=15 | | 3x+8=5x+9 | | -4f+1=13 | | 3x+7=2x+4 | | 125x=25x+1 | | 5m-12-3m=2m+8 | | -9d-1=17 | | 26x+2=18x+48x+6 |